I TINDAK TUTUR ILOKUSI PADA INTRAKSI JUAL BELI PEDAGANG DI PASAR CIPUTAT - Wijaya, Indra Cipta; ., Yamin (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2023)
This study examines the illocutionary speech acts that occur in the buying and selling interactions of traders in the Ciputat market. The purpose of this study is to describe illocutionary speech acts in the interaction of buying and selling of traders in the Ciputat market. The data in this study are the interaction speech of traders and buyers which are indicated to contain illocutionary speech acts in the buying and selling process at the Ciputat market which were obtained from recordings of the interaction of traders and buyers with details of traders and buyers selected by non-probability sampling with the convenience sampling technique, which means that the researcher has the freedom to choose whoever is found to be the sample. The method used is descriptive method. The research instrument was carried out using observation guidelines and documentation. The technique used to analyze the data obtained in the research is an interactive analysis technique. This technique has four components of analysis, namely: data collection, data reduction, data presentation, and drawing conclusions. The results of this study found (1) Assertive speech acts are characterized by the functions of declaring, demanding and telling, (2) directive speech acts are characterized by the functions of begging, offering, and suggesting, (3) expressive speech acts are characterized by complaining, apologizing, saying thank you, (4) commissive speech acts marked by guaranteeing, offering, and promising, (5) declarative speech acts marked by deciding